The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1742-6596/1569/2/022094
|View full text |Cite
|
Sign up to set email alerts
|

The hybrid whale optimization algorithm: A new metaheuristic algorithm for energy-efficient on flow shop with dependent sequence setup

Abstract: Recently, The industrial sector produces about half of the worlds total energy consumption. Manufacturing companies are required to reduce energy consumption. This article aims to develop a Hybrid Whale Optimization Algorithm (HWOA). We use the objective function of minimizing energy consumption. It solves the problem with permutation flow scheduling problems (PFSSP). Dependent sequence setup is a PFSSP problem with setups that depend on schedule sequence. We offer HWOA with local search strategies. The soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The light intensity of firefly x is represented with l and is proportional to the solution's objective function to be solved f(x). The attractiveness function is presented in equation (12). To obtain the value of the firefly's attractiveness, the calculation is conducted with distance (r).…”
Section: I( X1 ) = F(x)mentioning
confidence: 99%
See 1 more Smart Citation
“…The light intensity of firefly x is represented with l and is proportional to the solution's objective function to be solved f(x). The attractiveness function is presented in equation (12). To obtain the value of the firefly's attractiveness, the calculation is conducted with distance (r).…”
Section: I( X1 ) = F(x)mentioning
confidence: 99%
“…HFSS is one of the problems in NP-hard problems, which is also the generalization of the flow shop scheduling problem [8] [9] [10] [11]. In the flow shop scheduling problems, a series of jobs are ordered, and each job employs one machine in each stage [12] [13]. However, in HFSS, a series of jobs have similar production orders, but each stage's job might require one or more machines [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers call this problem energy-efficient scheduling (EES) [5]. EES is a scheduling problem that focuses on energy-efficient in the manufacturing process [6]. EES has received attention in recent years because it can reduce energy consumption without investment costs [7].…”
Section: Introductionmentioning
confidence: 99%
“…2). Several previous studies have shown that WOA has been effectively used in solving problems such as Inventory (Khalilpourazari et al, 2019), scheduling (Abdel-Basset et al, 2018;Utama et al, 2020c), Prediction (Osama et al, 2017), and Allocation (Yan et al, 2018). 3).…”
Section: Introductionmentioning
confidence: 99%
“…This research offers a Local search procedure to improve algorithm performance. It is a popular procedure to improve performance algorithm to solve the NP-Hard problem (Pop et al, 2013;Stodola, 2020;Utama et al, 2020c).…”
Section: Introductionmentioning
confidence: 99%